Synthesis and photocatalysis of Ag3PO4 nanoparticles loaded on ZnO nanostructure flowers - Anukorn Phuruangrat (2020)
© 2019, Australian Ceramic Society. Ag3PO4/ZnO nanocomposites were prepared by a deposition-precipitation method and were characterized by X-ray diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy, and X-ray photoelectron spectroscopy. The analytical results revealed the presence of cubic Ag3PO4 nanoparticles loaded on surface of three-dimensional self-assembled nanopetals of ZnO nanostructure flowers. The photocatalytic properties of Ag3PO4/ZnO nanocomposites were evaluated through photodegradation of methylene blue under ultraviolet radiation. In this research, Ag3PO4/ZnO nanocomposites showed higher photocatalytic activity than pure ZnO flowers.